Remarks on the movements and breeding grounds of the fur seal, based on observations made while on the United States naval patrol of Bering Sea in 1894 [electronic resource] - Brice, John J. ([Washington? : s.n., 1894)
Excerpt from the Report of Commissioner of Fish and Fisheries appendix 7. Caption title. Electronic reproduction. Mode of access: Internet. 44